2019
DOI: 10.1002/jtr.2289
|View full text |Cite
|
Sign up to set email alerts
|

Chinese venturers to Pacific Small Island Developing States: Travel and lifestyle

Abstract: This study emphasizes the necessity to understand the needs of the growing Chinese market, while also assessing how ready Small Island Developing States of the South Pacific are for these new visitors. Through a mixed method approach, combining individual visitor surveys and focus groups, this study investigates the lifestyle characteristics of outbound Chinese tourists to the Cook Islands and the motivation and travel behavior of these travelers. We refine a model for the travel lifestyle of Chinese tourists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In other countries in WHO's Western Pacific Region (WPR), Australia [10][11][12][13], New Zealand [14][15][16][17], and China [18], AMR is clearly a problem. Australia, New Zealand, and China have particularly close ties with Vanuatu and other PICTs through trade, investment, international aid, and seasonal workers [19][20][21]. Research into international travel and geographic trends in AMR has found that international mobility facilitates the spread of AMR [22].…”
Section: Number Culturedmentioning
confidence: 99%
“…In other countries in WHO's Western Pacific Region (WPR), Australia [10][11][12][13], New Zealand [14][15][16][17], and China [18], AMR is clearly a problem. Australia, New Zealand, and China have particularly close ties with Vanuatu and other PICTs through trade, investment, international aid, and seasonal workers [19][20][21]. Research into international travel and geographic trends in AMR has found that international mobility facilitates the spread of AMR [22].…”
Section: Number Culturedmentioning
confidence: 99%
“…In 2019, 26% of tourism outbound trips originated in the Asia‐Pacific region (UNWTO, 2020). Given the rise of Asian tourism (and Chinese tourism in particular) in recent decades, researchers have paid most attention to the Chinese outbound tourism market (Arlt & Burns, 2013; Li (Robert, 2016; Lau et al, 2019; Zhu et al, 2021), and to other Asian source countries and subregions (Bui & Trupp, 2020; Chang, 2015; Singh, 2009; Winter et al, 2008). Tourism certainly ceased to be a primarily Western phenomenon (Cohen & Cohen, 2014), where existing concepts of tourist motivations have been applied and further developed to other geographical and cultural contexts (Fu et al, 2017; Kau & Lim, 2005; Park & Yoon, 2009).…”
Section: Literature Review: Travel Motivation In a Pacific Contextmentioning
confidence: 99%
“…However, in a recent study Lau et al (2019) identified Chinese tourists' travel motivations to the Pacific SIDS, as they are receiving international investment from China and becoming a very strong destination choice for the Chinese tourist market. In this study they found that with the increase of internet coverage across China the majority of the Chinese tourists used blogs and social media platforms such as Trip Advisor as their main source of information before making decision and that their main motivations were related with enjoying family, exploring and interacting with different cultures, and they also enjoyed the exotic destination with low tourist density for true relaxation.…”
Section: Island Tourismmentioning
confidence: 99%